Psychological Factors Influencing Willingness to Purchase Wild–Edible Plants and Food Products from Wild–Edible Plants - Ana Težak Damijanić; Ana Čehić Marić; Milan Oplanić (Agriculture)
Modern agriculture faces many challenges. At the same time, it is necessary to provide healthy and sustainable food for humanity in growing conditions that are facing numerous problems, including climate change. Different strategies can be applied to deal with climate change, such as using different crop technologies. In this context, the application of wild–edible plants as a source of biodiversity, vitamins, and minerals for the human diet is interesting. Consumers’ behaviour toward wild–edible plants is a relatively new topic in marketing research, so this paper investigated the impact of certain psychological factors on consumers’ willingness to purchase wild–edible plants and food products. The study was performed on a sample of consumers of produce from farmers’ markets in Istria County, Croatia, and the data were collected via a questionnaire. The univariate and multivariate analyses provided evidence that consumers’ purchase intentions are determined mainly by their positive attitudes regarding trying new and unfamiliar foods. Furthermore, customers’ intentions to purchase food products containing wild–edible plants were determined by their attitudes regarding wild–edible plants and their subjective knowledge.